Entre o exercício da crítica e a escrita da história: o lugar de Sábato Magaldi na história do teatro brasileiro - Falcão, Letícia Fonseca (2017)
This master's thesis presents a contemplation about the production of the theatrical review of Sábato Magaldi and the writing of the history of Brazilian theater. The understanding of the subject and the places from which his thoughts emerge are the starting point for a finally thinking about his place in the construction of a historical narrative of our theater. From the analysis of texts of theatrical criticism, the consolidation of this critical discourse at the construction of a narrative about the group Teatro de Arena de São Paulo is exposed. Finally, the look at the panoramic works that try to show the trajectory of our theater, respond to the initial concerns of this work in order to understand the way the discourse of theatrical criticism is, sometimes reworked getting an air of historical narrative and occupying status of reference for research in the area.